2013
DOI: 10.1017/s0950268813002021
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and victim contact tracing of rabies virus from humans and dogs in Bali, Indonesia

Abstract: SUMMARYThe emergence of human and animal rabies in Bali since November 2008 has attracted local, national and international interest. The potential origin and time of introduction of rabies virus to Bali is described. The nucleoprotein (N) gene of rabies virus from dog brain and human clinical specimens was sequenced using an automated DNA sequencer. Phylogenetic inference with Bayesian Markov Chain Monte Carlo (MCMC) analysis using the Bayesian Evolutionary Analysis by Sampling Trees (BEAST) v. 1.7.5 software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 26 publications
1
25
0
1
Order By: Relevance
“…We previously reported that the ancestor of the Bali RABVs descended from the Kalimantan 00-18 strain, but did not differ significantly from the RABVs of Sulawesi and Flores [ 23 ]. Using a different dataset and a discrete analysis, we showed that the Bali strain originated from a relative of a Kalimantan RABV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the ancestor of the Bali RABVs descended from the Kalimantan 00-18 strain, but did not differ significantly from the RABVs of Sulawesi and Flores [ 23 ]. Using a different dataset and a discrete analysis, we showed that the Bali strain originated from a relative of a Kalimantan RABV.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of total RNA, as well as amplification of the N gene fragment and the primer sets used in this study have been described previously [ 23 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the victims (>80%) are children age 6-16 yrs transmitted by dog bite mainly in 99% cases and most of the deaths occur in Asia and Africa. A recent survey by Government of Bangladesh's Disease Control Unit of Ministry of Health indicates that the number of rabies death is at least 2335 per year and more than 300,000 persons receive post-exposure treatment per year [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various allegations seem to be hard to prove, but can only be proven to reveal the phylogenetic origin and a close kinship of the rabies virus. Of several isolates of rabies virus Bali that was analyzed showed that the rabies virus Bali form clusters apart, but have a close kinship with the rabies virus Sulawesi, Kalimantan and Flores (Mahardika et al, 2014) and regional rabies Indonesia has a close kinship with the rabies virus China, Malaysia, Laos, and Thailand, but it is closest to the rabies virus China (Heru Susetya, 2008). Nonetheless still required further study to more virus isolates from all districts / municipalities in Bali from all time periods since the outbreak of rabies that can be ascertained the validity of homology or genetic distance of the closest in the cluster with the rest of the rabies virus Bali, in addition to ensuring may have been a mutation or genetic recombination into a variant virus or novel virus given the use of various strains of the vaccine virus and the number of dog bite cases positive for rabies without showing any clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%